2006
DOI: 10.1002/pssc.200567104
|View full text |Cite
|
Sign up to set email alerts
|

Crystallographic and magnetic properties of a new rare‐earth iron nitride Nd2–xSmxFe17Ny (y ∼ 3)

Abstract: The effect of nitrogen insertion on the structural and magnetic properties of Nd 2-x Sm x Fe 17 metallic alloys has been investigated. X-ray powder diffraction characterizations show that all the nitrides are single phase and crystallize in the Th 2 Zn 17 -type structure. The lattice parameters of the Nd 2-x Sm x Fe 17 N y compounds decrease with samarium content. Magnetization studies show that all the samples are ferromagnetic at room temperature. Nitrogen insertion leads to an increase of the Curie temperat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2010
2010
2013
2013

Publication Types

Select...
3

Relationship

2
1

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 18 publications
(21 reference statements)
0
5
0
Order By: Relevance
“…We found that the calculated values of the magnetization are very close to the measured saturated magnetization at room temperature [12][13][14][15][16][17] when:…”
Section: Resultsmentioning
confidence: 91%
See 1 more Smart Citation
“…We found that the calculated values of the magnetization are very close to the measured saturated magnetization at room temperature [12][13][14][15][16][17] when:…”
Section: Resultsmentioning
confidence: 91%
“…In the present paper, the investigations are made by varying the concentration of the rare earths in (R 1−x R x ) 2 Fe 17 and (R 1−x R x ) 2 Fe 16 Co alloys. This study follows previous research on the intrinsic magnetic properties (magnetization and Curie temperature) of the same alloys [12][13][14][15][16][17]. The local information on the Fe sites obtained by Mössbauer spectrometry is compared with previous magnetic data.…”
Section: Introductionmentioning
confidence: 97%
“…The insertion of nitrogen has been carried out in static nitrogen gas under a pressure of 15 MPa at 733 K for 24 h. The nitrogen content was checked by the weight increase in the samples. It was found to be 2.9 ± 0.1 atoms per formula unit [5,6,12]. For these experiments a Brucker D8 powder diffractometer with the Co(K␣1) radiation ( = 0.1788970 nm) was used.…”
Section: Methodsmentioning
confidence: 99%
“…Nitrogenation induces a volume expansion of the lattice between 3% and 7%, leading to a large enhancement of both Curie temperature and magnetization [5,6]. Like their unnitrided counterparts, the R 2 Fe 17 N z compounds crystallize in a rhombohedral Th 2 Zn 17 structure for light rare-earths (Pr, Nd, Sm) [5,6], the nitrogen atoms being located predominantly on the 9e site [7].…”
Section: Introductionmentioning
confidence: 98%
See 1 more Smart Citation